Entrepreneurship - Hisrich, Robert D.; Peters, Michael P.; Shepherd, Dean A. (McGraw-Hill/Irwin, 2010)
This text is designed to instruct students on how to formulate, plan and implement a new venture. Students are exposed to descriptions of how to embark on a new venture in a logical manner, with actual case studies and entrepreneur profiles. The material is also supported by Internet resources.